Investigation of the effect of hydrocarbon spillages and their interaction with alteration minerals on the flotation of UG2 PGE ore - Tshinavhe, Thendo Arthur (Department of Chemical Engineering, 2024)
With growing safety, low productivity and operational cost concerns in the local PGE mining industry, mechanized mining is becoming more frequent to address these challenges and offer easy access to ore bodies compared to conventional mining methods. The heavy-duty machinery used may contaminate the ore because of oil inadvertently leaking from their hydraulic components during mining. Such contaminants have been anecdotally linked to the reduction of downstream flotation performance. Anecdotal evidence suggests that such problems are further exacerbated in the presence of phyllosilicate alteration minerals (serpentine, chlorite and talc) from weathered or altered ores. The near-surface Two Rivers Platinum (TRP) UG2 ore is routinely exposed to hydrocarbon contamination when the underground ore is excavated and transported to surface, resulting in reduced PGE flotation recoveries. Therefore, this study aimed to decouple the effects of oil contaminants on the flotation performance of PGE bearing ores and further establish the interaction mechanism(s) between oil and phyllosilicate alteration minerals. Two ores of varying alteration degrees (normal and altered UG2) were utilized to assess the effects of oil. Batch flotation tests were conducted to decouple the effect of oil on the flotation performance of the two UG2 ores by varying the oil dosage from 0 to 500 g/t, followed by conducting supplementary experiments in which the key interests were on column froth stability, rheology, and oil adsorption tests. These were performed to understand the mechanism(s) leading to the reduced flotation performance. Quantitative evaluation of minerals by scanning electron microscopy (QEMSCAN) was utilized to characterize the bulk mineralogy as well as PGM. The bulk mineralogy was validated with quantitative X-ray diffraction (QXRD). The last phase on the study involved using sodium metasilicate (1500 g/t) and a degreaser (500 g/t) as a potential mitigation measure to the deleterious effect of oil on flotation performance. As was expected, the QEMSCAN bulk mineralogy recorded a higher percentage of the phyllosilicate alteration minerals (serpentine, chlorite, and talc) in the altered UG2 (9.1 wt.%) relative to the normal UG2 (6.2 wt.%), consistent with the observations of alteration during sampling. Talc contributed around half of the total phyllosilicate alteration minerals in both ores; however, it was slightly higher in the altered UG2 compared to the normal UG2 (5.8 wt.% versus 3.8 wt.%). Therefore, the altered ore was expected to experience more severe detrimental flotation effects. The results of batch flotation tests indicated a decrease in Pt (~3 g.t) and Pd (~3 g/t) concentrate grades in the normal ore with increasing oil dosage with no significant negative effects on recovery (Pt increased by 4% and Pd was constant). In contrast, the oil resulted in detrimental effects to both Pt and Pd recovery for the altered ore, where a recovery loss of 6% Pt and 12 % Pd were observed. The concentrate grades remained unaffected. The addition of oil increased the froth stability for both ores (34% in the normal ore and 47% in the altered) as well as the pulp viscosity (including pure talc). The increase in viscosity was greater in the altered ore. The oil adsorption study on the two feeds revealed that most of the iv oil coats the particles with no preferential adsorption between the two ores (nearly the same concentration). The oil adsorption study on the concentrate and the tails showed no preferential recovery to either the concentrate or tails in the normal ore whereas more selective recovery of the oil-coated particles to the tails was observed for the altered ore. The observed decrease in grade in the normal ore due to oil contamination was attributed to oil improving the froth stability which caused excess entrainment of gangue materials and thereby diluting the concentrate grade. The decrease in recovery in the altered ore was ascribed to oil forming particle agglomerates (particularly complex talc agglomerates) which increased the pulp viscosity and subsequently resulting in poor gas dispersion and reduced particle-bubble collision. After understanding the mechanisms in each ore, batch flotation with sodium metasilicate and a degreaser were conducted in the presence of oil, as a potential mitigation measure. Sodium metasilicate (SS) improved the grades in the normal ore floats and had no detrimental effect toward the recovery (constant recoveries, no loss in Pt and Pd). For the altered ore, both the grade and recovery (Pt-8% and Pd-5%) were improved by the adding of SS. The effects on the grade were most noticeable at low oil concentration (0 and 300 compared to 500 g/t). For the degreaser, only the flotation experiments with the degreaser were performed due to laboratory technical problems-new flotation cell was used. Thus, there was no comparison with the no degreaser condition. The trends (% difference between 0 g/t and 500 g/t) were compared to the no degreaser (oil only) conditions conducted in the first cell. The degreaser was shown to improve 2E grade and recovery in both ores. However, the improvement in flotation performance was unquantified. The deleterious effects were successfully mitigated when using sodium metasilicate due to its beneficial effects in reducing pulp viscosity as well as improving the froth drainage. With the degreaser, the flotation performance was not quantified. Therefore, this study demonstrated that, SS can be implemented to mitigate the viscous effects caused by oil spillages and alteration minerals (particle agglomeration) in mechanized mines. However, SS should not be implemented blindly as other downstream processes should be considered (settling in the thickener). To implement the degreaser, more tests need to be conducted.